Further progress in the characterisation of complex radiation fields - Spurny, Frantisek; Silari, Marco (Radiation protection dosimetry, 2008)
One of the topics which forms part of CONRAD project addresses the problems related to the dosimetry of complex-mixed radiation fields at workplaces. This topic was included in work package (WP) 6. WP 6 was established to co-ordinate research activities in two areas:the development of new techniques and the improvement of current techniques for characterisation of complex workplace fields (including high-energy fields and pulsed fields): measurement and calculation of particle energy and direction distributions (Subgroup A); and model improvements for dose assessment of solar particle events (Subgroup B). In both cases in order to aid the research, WP 6 increases the efficiency of resource utilisation, and facilitates the technology transfer to practical application and for the development of standards. This contribution presents a general overview of activities of SG A; specific results related to the benchmark experiment at GSI Darmstadt are presented separately, and will be published in other way. As far as the results acquired in the frame of the SG B activities, these are presented in the meeting held as part of EURADOS AM 2008.
Keywords: dávka záření; Švýcarsko; Evropská unie; Occupational Exposure; záření; Computer Simulation; pracovní expozice; teoretické modely; European Union; Radiation Dosage; Models, Theoretical; lidé; Monte Carlo Method; Humans; Switzerland; metoda Monte Carlo; Environmental Exposure; počítačová simulace; Radiation; sluneční aktivita; monitorování radiace; vystavení vlivu životního prostředí; Solar Activity; Radiation Monitoring